T Cell Response Toward Tissue-and Epidermal-Transglutaminases in Coeliac Disease Patients Developing Dermatitis Herpetiformis - Caproni, Marzia; Capone, Manuela; Rossi, Maria Caterina; Santarlasci, Veronica; Maggi, Laura; Mazzoni, Alessio; Rossettini, Beatrice; Renzi, Daniela; Quintarelli, Lavinia; Bianchi, Beatrice; Ninci, Alessandra; Lami, Gabriele; et al. (Frontiers in Immunology, 2021)
The reason why only few coeliac patients develop the cutaneous manifestation of the disease, named dermatitis herpetiformis (DH), is still unknown. Epidermal transglutaminase (TG3) has been described as the main autoantigen of humoral immunity in DH but the mechanisms leading to this autoimmune response remain obscure. Here we characterized T cells from skin, gut and peripheral blood of DH and coeliac disease (CD) patients, evaluated the impact of the gluten-free diet on circulating T lymphocytes’ phenotype and investigated antigen specific T cell response toward epidermal and tissue transglutaminase (TG2). DH patients showed an increased frequency of skin-derived T cells producing TNFα when compared to CD patients. Moreover, circulating T cells producing TNFα and IL-17A positively correlated with clinical score of skin disease activity and decreased after gluten-free diet. Finally, TG2 and TG3-specific T cells resulted more reactive to antigens stimulation in DH patients and showed cross reactivity toward the two autoantigens in both the group of patients. Our data suggest a role of TNFα and IL-17A producing cells in the development of DH and, for the first time, show the existence of a crossed T cell response toward the two transglutaminases isoforms, thus suggesting new insights on T cells role in skin damage.